CORRELATES OF KNOWLEDGE LEVEL OF FARMERS IN SONITPUR DISTRICT OF ASSAM (Indian Journal of Animal Production and Management, 2015)
The study was conducted on 100 broiler farmers of Sonitpur district of Assam in order to find out their socio-economic status, level of knowledge in scientific broiler farming and relationship of knowledge level with their socio-economic status. It was revealed that majority of the respondents were young having passed high school, with marginal land holding, small flock size, short length of experience in broiler farming and low level of participation in training and low level of extension contact and low mass media exposure. Majority had low level of knowledge in scientific broiler farming and two variables viz. Education and experience were found to have significant relation with knowledge level.
Keywords: Broiler farming; knowledge; socio-economic status